The application of supercritical CO2 in nuclear engineering: A review. (December 2018) - Qi, Houbo; Gui, Nan; Yang, Xingtuan; Tu, Jiyuan; Jiang, Shengyao
Due to its advantages of low critical pressure and temperature, stability, non-toxic, abundant reserves and low cost, supercritical CO2 becomes one of the most common supercritical fluids in modern researches and industries. This paper presents an overview focusing on the researches of supercritical CO2 in nuclear engineering and prospects its applications in the field of nuclear industry. This review includes the recent progresses of supercritical CO2 research as: (1) energy conversion material in both recompression cycle and Brayton cycle and its applicability in Generation IV reactors; (2) reactor core coolant in the Echogen power system and reactors at MIT, Kaist and Japan, and other applications, e.g. hydrogen production. Based on the rapid progress of research, the supercritical CO2 is considered to be the most promising material in nuclear industries.